2018
DOI: 10.4103/jnrp.jnrp_390_17
|View full text |Cite
|
Sign up to set email alerts
|

Using of Fresh Cadaveric Cow Brain in the Microsurgical Training Model for Sulcal-Cisternal and Fissural Dissection

Abstract: Objective:The aim of this experimental study was to evaluate the feasibility of using fresh cadaveric cow brain as in a training model for microsurgical dissection of sulcus, cisterns, and fissure.Methods:Experimental microneurosurgical activities in this study were performed under the operating microscope. Bilateral sylvian cisterns, interhemispheric fissure, and hemispheric sulcus of the fresh cadaveric cow brain were used as an interested area for this experimental study. The dissection was continued reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In a more recent study, cerebral dissection on cow brains was also achieved by Gokyar et al [34] who dissected bilaterally the sylvian cisterns, as well as the interhemispheric fissure and hemispheric sulcus.…”
Section: Bovine Modelsmentioning
confidence: 99%
“…In a more recent study, cerebral dissection on cow brains was also achieved by Gokyar et al [34] who dissected bilaterally the sylvian cisterns, as well as the interhemispheric fissure and hemispheric sulcus.…”
Section: Bovine Modelsmentioning
confidence: 99%
“…More recently, Gökyar et al [31] used fresh cadaveric cow brains to microscopically dissect the Sylvian cisterns, interhemispheric fissure, and hemispheric sulcus. The authors concluded that the models were useful aids for microsurgical training.…”
Section: Task-oriented Simulation Trainingmentioning
confidence: 99%
“…32 Bovine (Bos taurus) is a promising source for brain ECM studies in the neuroscience field as bovine brain has high similarity to human brain, with its large size and gyrencephalic structure, which is the state of folding and convolutions within the cerebral cortex. 34,35 Another advantage of using bovine tissues in 3D culture experiments is their easy accessibility from local slaughterhouses. 34 Recently, various bovine tissues, such as ovarian tissue, 36 flexor tendons, 37 retina, 38 spinal cord meninges, 39 endometrium, 40 vocal fold 41 and lung, 42 were used as a source in decellularization procedures to fabricate hydrogels.…”
Section: Introductionmentioning
confidence: 99%